Enzymatic Assay of Immobilized β-D-Galactosidase Enzyme on Magnetite Nanoparticle - Al-Hajjar, Ruaa Lateef Noor; Taha, Ekhlass M.; Farhan, Ahlam M.; Shaalan, Naser (Iraqi Journal of Science, 2023)
According to the high operational costs, low stability, and reusability of enzymes, immobilization by nanoparticle gathering has increased in recent years. Iron oxide nanoparticles (magnetite nanoparticles, Fe₃O₄) have been prepared by mixing one volume of iron dioxide ions and two volumes of iron trioxide ions with HCl via the precipitation of iron salts by NH₄OH. The features of magnetic nanoparticles have been studied by Atomic Force Microscopy (AFM), X-Ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy, and Scanning Electron Microscopy (SEM). The prepared Fe3O4 was used in the adsorption method to immobilize the galactosidase enzyme. The immobilized enzyme has been compared with the crude one by optimizing time, PH, temperature, substrate solution concentration, and enzyme solution concentration. As a result, the immobilized enzyme has exhibited higher activity over long storage times, and a wide PH and temperature range than crude enzyme. In addition, whatever the substrate and enzyme concentrations, the activity of the immobilized enzyme increased over the non-immobilized one. As a result, a lower Km value for immobilized D-galactosidase indicates a higher affinity for the substrate than crude D-galactosidase.